Development and Validation of Contextualized Learning Materials in Grade 5 Pupils’ Math Word Problem- Solving in Selected Schools in North 2 District, Division of Gingoog City - Valerie Cleofe D. Pahalla; Isidro M. Biol, Jr (Randwick International of Education and Linguistics Science Journal, 2026)
This study developed and validated contextualized learning materials to address the least learned mathematical word problem-solving competencies of Grade 5 learners in selected schools in the North 2 District, Division of Gingoog City. Employing a developmental research design guided by the Analysis, Design, Development, and Evaluation (ADDE) model, the study analyzed the consolidated Beginning-of-School-Year Rapid Mathematics Assessment (BoSY RMA) results of 39 Grade 5 learners from San Jose Elementary School and Malibud Central School. Findings revealed that the most difficult competencies involved adding dissimilar fractions including mixed numbers (79.5%), solving multi-step problems involving multiplication of decimals (79.5%), illustrating and describing solid figures and their nets (71.8%), and interpreting data presented in tables and line graphs (48.7%). Based on these identified learning gaps, a contextualized workbook entitled Where Math Meets Life was developed. The workbook integrated community-based situations, real-life applications, guided examples, visual representations, vocabulary support, and progressive learning activities aligned with the Grade 5 Most Essential Learning Competencies (MELCs). The developed materials were evaluated by mathematics and language experts using the Department of Education Learning Resources Management and Development System (LRMDS) evaluation tool. Results indicated very high validity in both content and language, confirming the instructional quality, curriculum alignment, readability, and suitability of the materials for Grade 5 learners. A clustered Learning Action Cell (LAC)-based implementation plan was likewise proposed to facilitate future utilization of the validated workbook.